Islamic Legal Perspective On Business With An Online Deposit Service System In Social Media - Rafika Nursyahida; Shanty Hermalia Putri; Ulfa Safira Saliha; Achmad Zulfikar Siregar (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2022)
Online delivery service is a business that provides buying and selling services to people to buy something, which is then added as a fee which is called entrusted service fee. The problem in this research is how is the perspective of Islamic law towards business with an online entrusted service system through social media. Data collection in this writing uses the method of reviewing several sources of books, journals and sharia economic websites as research libraries. From the results of this study it can be concluded that basically entrusted services are permitted in Islamic law. If the entrusted service has fulfilled the pillars and conditions. Buying and selling entrusted services through social media is not a practice of buying and selling other people's property. The agreement between the entrusted service provider and the seller is made orally.